Dinâmica da cobertura da terra e carbono em 55 assentamentos na Amazônia Legal entre 2008 e 2016: implicações para políticas de mudanças climáticas - Iris Roitman; Rômulo José da Costa Ribeiro; Tamiel Khan Baiocchi Jacobson; Luciana Silva Estevam; Nívea Jorgia Silva Marcondes; Reinaldo José de Miranda Filho; Ludgero Cardoso Galli Vieira; Sílvia Starling Assad; Mário Lúcio Ávila (Confins)
In this study, we described the dynamics of land-cover and gross carbon stocks and emissions (C) in 55 settlements in Legal Amazon, located in northern Mato Grosso state, between 2008 and 2016 and discussed their implications for climate change policies. C estimates were based on land-cover changes, obtained with Spot, Sentinel and Landsat image processing and field visits, and secondary data of mean carbon values ​​per vegetation class. The 55 settlements were originally covered by 685,000 ha of native vegetation (103 Tg C). Deforestation by 2016 was over 65%. Most of it (77%) occurred by 2008. Although restoration of consolidated areas (areas deforested before July 2008) is not mandatory, it can generate revenue from carbon credits, environmental reserve quotas, forest management and agroforestry. The deforested area per settlement by 2008 was strongly related to the deforestation per settlement between 2008 and 2016. This suggests that those who deforested a lot until 2008 tend to continue to do so until 2016. The annual deforestation rate between 2008 and 2016 was 12.7 thousand ha /year. If it remains the same, all native vegetation will have been suppressed in less than two decades. In general, the Sustainable-Development-Project settlements had less deforestation, which indicates that it is possible to associate agrarian reform and economic and social development with the conservation of the Amazon rainforest. However, it is necessary to strengthen policies toward payment for ecosystem services and forest management products (low-impact forest management and non-timber forest products). In order to do so, the integration of federal, state and local governments and market efforts is paramount.